Analisis Kesiapan Guru Dalam Pembelajaran Jarak Jauh Saat Covid-19 - Nasya Auliarahma Sidqi; Pipin Auliya (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2020)
This study aims to analyze the readiness of elementary school teachers in facing distance learning. This study is motivated by the importance of primary school teacher readiness for distance learning. This can be seen from three aspects, namely: 1) teachers' understanding of distance learning; 2) the ability of teachers to apply media to meet distance learning; 3) supporting factors and constraints in implementing study from home or distance learning. This research uses a qualitative approach, through interviews, observation and documentation. The subjects of this research are educators in Kartasura who carry out Distance Learning. Then the validity of the research was carried out through member cheking. The results showed that the teachers' understanding of distance learning and the application of learning had been done well by the teachers. Although there are many obstacles in using technology and learning media. This condition requires teachers to increase confidence and work ethic in all circumstances. In the scientific discipline this research provides information about the existence of various obstacles in the implementation of PJJ. One of them is seeing the readiness of educators.